Resolving Hexose-Phosphates by LC-MS Leads to New Insights in PGM1-CDG Pathophysiology - Driesen, Karen; De Craemer, Sam; Morava, Eva; Cassiman, David; Witters, Peter; Ghesquière, Bart (ACS omega)
Hexose-phosphates play a role in many metabolic pathways, such as glycolysis and glycosylation. To understand the molecular basis of diseases such as congenital disorders of glycosylation (CDG), information about the source and abundance of hexose-phosphates is imperative. Mass spectrometry (MS)-based tracer metabolomics can provide this information, but hexose-phosphates are structural isomers with similar physicochemical properties, which makes them difficult to differentiate using MS. Here, we present and compare two optimized liquid-chromatography-based MS methods for the identification of relevant hexose-phosphates, compatible with tracer metabolomics. A combination of these two methods led to the analysis of eight hexose-monophosphates and two hexose-bisphosphates that can occur in humans. Both methods displayed linearity in 3 to 4 orders of magnitude, with limits of quantification between 0.5 and 50 nM, which is well within the cellular concentration range. The applicability of these methods to biological models was then proven in a study of the effect of galactose treatment in phosphoglucomutase 1 (PGM1)-CDG fibroblasts. Here, we show, for the first time, the hexose-phosphate profiles in CDG and how these change upon treatment.